IMPLEMENTASI PERATURAN GUBERNUR BANTEN NOMOR 46 TAHUN 2022 TENTANG KEDUDUKAN, STRUKTUR ORGANISASI, TUGAS POKOK DAN FUNGSI, URAIAN TUGAS, DAN TATA KERJA SEKRETARIAT DEWAN PERWALIAN RAKYAT DAERAH DI SEKRETARIAT DPRD PROVINSI BANTEN - Edi Suhaedi; Suwaib Amiruddin; Titi Stiawati (Sawala : Jurnal Administrasi Negara, 2025)
Article should be started by Title of Article followed by Authors Name and Affiliation The implementation of Banten Governor Regulation (Pergub) No. 46 of 2022 concerning the Position, Organizational Structure, Main Duties and Functions, Job Descriptions, and Work Procedures of the Banten Provincial DPRD Secretariat is a strategic step to strengthen the institutional governance of the regional legislature. This study aims to analyze the effectiveness of the implementation of the regulation in improving the performance of the Banten Provincial DPRD Secretariat as the main support for the legislative, budgetary, and supervisory functions of the DPRD. The research method used a qualitative approach with data collection techniques through in-depth interviews with 10 informants (DPRD Secretariat officials, DPRD members, and related parties), document studies, and observation of work processes. The results showed that the implementation of Governor Regulation 46 Year 2022 has provided clarity on the organizational structure, division of tasks, and coordination mechanisms between units, thus improving the efficiency of administrative services and technical support to DPRD members. However, there are still challenges in optimizing the Secretariat's functions, such as limited qualified human resources (HR), lack of internal socialization of the new work procedures, and the need for technological adaptation to support the digitization of the legislative process. Other findings revealed that the pergub also emphasized the Secretariat's position as a neutral and professional regional apparatus, although local political dynamics sometimes affect performance independence. Recommendations include increasing the capacity of human resources through technical training, strengthening the internal monitoring system, and synergizing with local governments to ensure adequate budget allocations. This study concludes that the successful implementation of Governor Regulation 46 Year 2022 is highly dependent on the commitment of all stakeholders in translating the regulation into consistent operational practices, thus supporting the realization of transparent and accountable DPRD governance